Property rights and the management of animal genetic resources: how to secure access to drylands resources for multiple users - Anderson, Simon; Centose, Roberta (International Food Policy Research Institute, 2006)
Genetic erosion in animal genetic resources (AnGR) is of concern where livelihoods of the poor are affected and option values for society are being lost. The poor often live in marginal areas and their livestock maintain adaptive characteristics. However, processes leading to genetic erosion do not precipitate adaptation through natural selection. This paper explores how local property rights systems in poor communities for AnGR are organized. The dynamism and dialectical aspects of these systems are considered and the impact of their breakdown assessed in terms of AnGR diversity. The conservation of AnGR option values through livestock husbandry by the poor is a hitherto unrecognized and unrewarded service to society.